Padronização da ecocardiografia em rottweilers saudáveis e efeito da acepromazina, meperidina e sua associação - Reis, Afonso Cassa (2015)
The echocardiogram (ECO) is an exam widely used in veterinary medicine for the diagnosis of heart disease, but even being a noninvasive exam, dogs can not collaborate with the appropriate positioning for the examination. To reduce the animal's agitation and improve the quality of the images, sedation could be used. Also, a wide range of weight and body conformation found in different breeds of dogs can be a limiting factor in the interpretation of echocardiographic examination. The objective of this study was to evaluate the effects of sedation with meperidine, acepromazine and its association on the echocardiographic parameters in dogs (chapter 1) and to estabilish the normal echocardiographic parameters in Rottweilers (chapter 2). In chapter 1, 12 healthy adults Rottweilers were used. Each dog was subjected to the echocardiography examination without the use of sedation (control treatment- CT) and subjected to three treatment protocols using meperidine (2 mg / kg) (MT), acepromazine (0.05 mg / kg) (AT), and the combination of drugs (MAT), at the same dosage. The variables were analyzed by Tukey test to determine differences between treatments, with 5% significance level. It was observed that the average obtained in A-wave of mitral inflow in AT and MAT decreased significantly comparing with MT, which did not differ from CT. There was a significant decrease in the measure of mitral annulus motion MAM and tricuspid annular plane systolic excursion (TAPSE) at TA. There was no significant difference to the FE values between TA and other treatments. However, it was observed that 57.3% of the dogs showed FE values below the normal range for the species. The changes found may be due to the hypotensive effects of acepromazine used in isolation. It was concluded that meperidine or its association with acepromazine not alter echocardiographic parameters in healthy dogs and that acepromazine, used alone, causes changes in systolic function and is not recommended for sedation of dogs submitted to echocardiography exam. It was selected 23 clinically healthy adult dogs, 15 females and 8 males, with average weight of 43.3 ± 4.5 kg and mean age of 42.5 ± 14.8 months. Mean and standard deviation was determined of all echocardiographic parameters and Pearson correlation was performed between weight, age,sex and other variables analyzed, with 5% significance level. Echocardiographic parameters were compared by descriptive analysis with the normal values for the canine general population. There was a significant positive correlation between age and heart rate and LVDd; and significant negative correlation between age and the E and A waves of the mitral inflow. The greater the body weight, the higher the maximum speed of the Doppler aortic flow assessment. There was no significant correlation between sex and any parameters evaluated. The individual assessments and the means of echocardiographic parameters, it was observed that the values When, AE, IVSD and MAM presented themselves smaller than the determined general pattern in dogs; and DLVs and PLVEd values had become larger and may be an inherent characteristic of the breed.